Palmoplantar keratosis in oculodentodigital dysplasia with a GJA1 point mutation out of the C‐terminal region of connexin 43. Issue 12 (12th November 2014) - Kogame, Toshiaki; Dainichi, Teruki; Shimomura, Yutaka; Tanioka, Miki; Kabashima, Kenji; Miyachi, Yoshiki
Abstract Gap junction proteins are composed of 21 genes of the connexin (Cx) family. They play important roles in cell–cell contact by exchange of small molecules through hemichannels. Hence, mutations of Cx family genes affect various tissues of a body. The mutation of the GJA1 gene, which codes Cx43, causes oculodentodigital dysplasia (ODDD), commonly in an autosomal dominant manner with phenotypic variability. It has been believed that gene mutations causing truncation of the Cx43 C‐terminus is necessary and sufficient for palmoplantar keratosis (PPK) development in ODDD patients. Here, we report a case of an ODDD patient developing PPK with a GJA1 gene mutation (c.412G>A/p.Gly138Ser), which was previously reported in a case of ODDD without PPK and expected not to result in C‐terminal truncation of Cx43. This case suggests not only C‐terminal truncation, but also that a point mutation in the cytoplasmic region of Cx43 can cause PPK in ODDD patients.